TEORI BELAJAR KONSTRUKTIVISME DAN APLIKASI NYA DALAM PEMBELAJARAN BAHASA ARAB - Miswarul Abdi Aziz; Teuku Sanwil (Pedir Research Institut, 2022)
Learning according to constructivism theory is building knowledge little by little, which is then expanded through a limited context and not suddenly. Knowledge is not a set of facts, concepts or rules that are ready to be retrieved or memorized. Humans must construct that knowledge and give meaning through real experience. In the learning process in the classroom, students need to be accustomed to solving problems, finding something useful for themselves, and struggling with ideas. Teachers will not be able to provide all knowledge to students. Students must construct knowledge in their own minds. Students must find and transform complex information into other situations. On that basis, learning and learning must be packaged into a process of “constructing” not receiving “knowledge. Basically constructivism theory here is defined as an approach in which students must individually find and transform complex information, examine information with existing rules and revise it if necessary. The basic concept of constructivism is an element where a person can actively build his knowledge by comparing new information with his existing understanding. Constructivism theory views students as individuals who are always active and can find ways of learning that suit themselves. Meanwhile, the teacher only functions as a facilitator, mediator and friend who creates a conducive atmosphere for the construction of knowledge in students.